A novel antibody discovery platform identifies anti-influenza A broadly neutralizing antibodies from human memory B cells. Issue 5 (3rd July 2016) - Xiao, Xiaodong; Chen, Yan; Varkey, Reena; Kallewaard, Nicole; Koksal, Adem C.; Zhu, Qing; Wu, Herren; Chowdhury, Partha S.; Dall'Acqua, William F.
ABSTRACT: Monoclonal antibody isolation directly from circulating human B cells is a powerful tool to delineate humoral responses to pathological conditions and discover antibody therapeutics. We have developed a platform aimed at improving the efficiencies of B cell selection and V gene recovery. Here, memory B cells are activated and amplified using Epstein-Barr virus infection, co-cultured with CHO-muCD40L cells, and then assessed by functional screenings. An in vitro transcription and translation (IVTT) approach was used to analyze variable (V) genes recovered from each B cell sample and identify the relevant heavy/light chain pair(s). We achieved efficient amplification and activation of memory B cells, and eliminated the need to: 1) seed B cells at clonal level (≤1 cell/well) or perform limited dilution cloning; 2) immortalize B cells; or 3) assemble V genes into an IgG expression vector to confirm the relevant heavy/light chain pairing. Cross-reactive antibodies targeting a conserved epitope on influenza A hemagglutinin were successfully isolated from a healthy donor. In-depth analysis of the isolated antibodies suggested their potential uses as anti-influenza A antibody therapeutics and uncovered a distinct affinity maturation pathway. Importantly, our results showed that cognate heavy/light chain pairings contributed to both the expression level and binding abilities of our newly isolated VH1-69 family, influenza A neutralizing antibodies, contrasting with previous observations that light chains do not significantly contribute to the function of this group of antibodies. Our results further suggest the potential use of the IVTT as a powerful antibody developability assessment tool.